Dentistry Education Innovation during the COVID-19 Pandemic in the World in 2020 – 2022 - Pindobilowo; Tuti Alawiyah; Dwi Ariani; Irma Binarti (Formosa Journal of Applied Sciences, 2023)
Introduction: the teaching and learning process in the Faculty of Dentistry around the world during the COVID-19 Pandemic has a challenge, where institutions must continue to carry out educational processes for the community and produce quality dentists. Purpose: to find out the educational process of dental faculties in the world during the COVID - 19 Pandemic. Methods: using a narrative review with online databases and the BMC Oral Health website, PubMed, and Google Scholar. The references used are from 2021 - 2022. Conclusion: Dentistry students can play a role in preventing and handling the COVID-19 outbreak by embedding E-learning and government regulations are needed in the teaching and learning process.